A novel hybrid adsorption heat transformer – multi-effect distillation (AHT-MED) system for improved performance and waste heat upgrade. (1st January 2022) - Saren, Sagar; Mitra, Sourav; Miyazaki, Takahiko; Ng, Kim Choon; Thu, Kyaw
Graphical abstract: Highlights: Developed the hybrid AHT-MED system for improved performance of desalination. Exploits the adsorption potential to upgrade the waste heat to a higher temperature. The system extends the temperature difference between TBT and BBT. Water production rate of AHT-MED is twice that of the MED for the same heat source. Abstract: Multi-effect distillation (MED) systems are considered to be the most energy-efficient thermal desalination methods. This paper introduces the development of a novel thermal desalination system for performance superior to MED systems for the same operating temperature limits. Such an unprecedented achievement was attained by upgrading the heat source using the chemical potential of adsorption phenomena. The proposed Adsorption Heat Transformer (AHT) cycle hybridized with Multi-effect distillation system (AHT-MED) exhibits higher performance ratio and water production rate than a conventional MED system for the same heating source and sink. The heat generated by the heat of adsorption with the temperature higher than the heat source is supplied to the first effect of the MED system, thus, extending the temperature difference between the Top Brine Temperature (TBT) and Bottom Brine Temperature (BBT). The higher temperature difference offers more number of effects, with the equivalent temperature difference between the effects (ΔTe ) as the design parameter. Using the low-temperature heat source (as low as 58 °C), the system can employ an increased number of effects (as high as 11) due to the supply of heat at an increased temperature of around 80 °C. The proposed system achieves a higher performance ratio (approximately 5.4) and water production rate (2 kg/s) compared to the standalone MED system (PR: 4.2, WPR: 1 kg/s) with the number of effects of the hybrid system as 10 at constant interstage temperature difference between the standalone and hybrid systems. This novel AHT-MED system opens up new possibilities for low-temperature heat source-driven thermal desalination with significantly improved performance.